2019
DOI: 10.1080/00222895.2019.1689909
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Movement-Inducing Effects of Music through the Fractality of Head Sway during Standstill

Abstract: The links between music and human movement have been shown to provide insight into crucial aspects of human's perception, cognition, and sensorimotor systems. In this study, we examined the influence of music on movement during standstill by analyzing head sway fractality, with the aim of further characterizing the correspondences between movement, music, and cognition. Eighty seven participants were asked to stand as still as possible for 500 seconds while being presented with alternating silence and musical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…We did not find a significant effect of the rhythmic complexity on the movement responses. While this may seem surprising, it is in line with the results from a different study using the same stimuli (González Sánchez et al, 2019). One explanation for the lack of significance here may be that it is primarily the presence of a steady beat that drives the spontaneous movement responses.…”
Section: Musical Complexitysupporting
confidence: 87%
See 4 more Smart Citations
“…We did not find a significant effect of the rhythmic complexity on the movement responses. While this may seem surprising, it is in line with the results from a different study using the same stimuli (González Sánchez et al, 2019). One explanation for the lack of significance here may be that it is primarily the presence of a steady beat that drives the spontaneous movement responses.…”
Section: Musical Complexitysupporting
confidence: 87%
“…We have studied micromotion using an experimental paradigm in which subjects are asked to stand still on the floor while listening to music (Jensenius et al, 2017). From these studies we have found that people's micromotion is on average higher when listening to music than when they stand still in silence, even when they deliberately try not to move (Jensenius et al, 2017;González Sánchez et al, 2018;González Sánchez et al, 2019). Different types of music seem to influence the micromotion in various ways.…”
Section: Music-related Micromotionmentioning
confidence: 99%
See 3 more Smart Citations